The Role of Social Companions in the Success of PKH Independent Prosperous Graduation: a Study in Pedes District, Karawang - Liya Yulia (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Graduation Mandiri is a measure of the success of the Family Hope Program (PKH) which can make participants graduate independently. This objective positions the PKH facilitator as an essential change agent for the program is success. As a result, this study will explain in detail how PKH facilitators might encourage benefit families (KPM) to graduate on their own. This study uses a qualitative method with a descriptive approach. There were 11 research informants, which included program participants including mentors, independent graduate students, and the government. According to the study's findings, the facilitator plays four different roles: one that is facilitative by encouraging KPM PKH to meet their basic needs and increase the productivity of benefits who have graduated on their own; two that are educational by enhancing knowledge and hard skills through Family Development Session programs and vocational trainings; three that are represented by establishing connections between KPM and different source systems that can help them grow their businesses; and are technical by encouraging KPMs to improve their own performance.